Pengenalan Makanan Tradisional dan Peningkatan Rasa Cinta Tanah Air melalui Materi Etnomatematik pada Siswa SD Negeri Genuk 01 - Yogi Ageng Sri Legowo; Waskito Aji; Muhammad Muhammad; Dwi Aizah; Rio Dwi Permana (Jurnal Kemitraan Masyarakat, 2025)
Traditional food is a national asset. It not only serves as a source of energy for the community, but also serves as a form of food security, an economic driver, a source of healthy food, and a culture steeped in noble values. The widespread consumption of unhealthy foods by students, especially elementary school students, is one of the reasons for this outreach activity. The health issues surrounding junk food must be addressed by offering healthy alternatives, such as traditional foods. Traditional food is not only related to food, but can also be linked to ethnomathematics, where culture in the form of food is studied from a mathematical perspective. Elementary school students not only consume traditional foods but also interpret these foods in mathematical contexts, such as geometry and numbers. In this way, students will be able to visualize mathematical elements not only when reading math textbooks but also when consuming traditional foods that are part of their daily environment. Despite their traditional nature, students actually enjoy some traditional foods. This is a frequent conflict between the current generation and traditional culture. They better understand how to prepare traditional foods, appreciate the richness of local culture, and develop a love for their culture and homeland.